Architecture of reliable Web applications software - Radaideh, Moh'd A., 1965-; Al-Ameed, Hayder, 1969- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book presents new concepts regarding reliability, availability, manageability, performance, scalability, and secured-ability of applications, particularly those that run over the Web. It examines causes of failure in Web-based information system development projects, and indicates that to exploit the unprecedented opportunities offered by e-service applications, businesses and users alike need a highly available, reliable, and efficient telecommunication infrastructure"--Provided by publisher.